ANALYSIS OF SPEED RUNNING AND INDEX OF POLES USED BY FINALISTS OF POLE VAULT JUMPING IN 2014 NATIONAL CHAMPIONSHIP FINAL - Cristian GRAUR; Barna SZABÓ-CSIFÓ (Cluj University Press, 2016)
Pole vault jumping is one of the most complex athletic events. The level of each athlete on physical qualities are considered a condition sine qua non in achieving high-level results in pole vaulting. Determinate the specific speed parameters on the last part of the approach and grip characteristics of hardness and height used by the finalists in 2014 Senior National Championship. The speed parameters on last part of the approach were measured with Microgate Time Racer2, a device consisting of three pairs of placed photocells. Features of the poles used by the first three finishers in the National Championship Final were monitored during the competition. The first three finalists in 2014 Seniors National Championship Final, obtained specific speed parameters with values between 7.9 m/s and 8.8 m/s on the last 5 m of approach right before the take of phases and detachment. From the point of view of the used poles, they used poles with stiffness index, values between 75 kg and 82 kg. Grip heights were 4.50 m and 4.64 m. All these parameters led to crossing height between 4.85 m and 5.11 m by the first three finishers in the monitored contest. A higher value of speed parameters, hardness -elasticity and the grip of used pole have as repercussions the achievement of good results in the pole vaulting event. Analiza vitezei pe elan și a caracteristicilor prăjinilor folosite de finaliștii probei de săritura cu prăjina la finala campionatului național 2014. Proba de săritură cu prăjina este una dintre cele mai complexe probe atletice. Nivelul fiecărui atlet privind calitățile fizice reprezintă o condiție absolut necesară în vederea atingerii unor rezultate cât mai bune în probă. Parametrii de viteză pe ultima parte a elanului au fost determinați cu ajutorul dispozitivului Microgate Time Racer 2, Caracteristicile prăjinilor folosite de primii trei clasați în finala Campionatului Național au fost monitorizate în timpul desfășurării concursului. Primii trei clasați în Finala Campionatului Național de seniori ediția 2014 au obținut parametrii de viteză specifică cu valori cuprinse între 7,9 m/s și 8,8 m/s pe ultimii 5 m de alergare pe elan, chiar înaintea fazei de prezentare și desprindere. Din punct de vedere al caracteristicilor prăjinilor folosite, aceștia au folosit prăjini cu indice de duritate cu valori între 75 kg și 82 kg. Înălțimea prizelor a fost de 4,50 m și 4,64 m. Toți acești parametrii au dus la trecerea peste înălțimi între 4,85 m și 5,11 m de către primii 3 clasați în concursul monitorizat. O valoare cât mai mare a parametrilor de viteză, duritate-elasticitate și priză a prăjinii folosite au repercusiuni în obținerea de rezultate bune la proba de săritură cu prăjina.  Cuvinte-cheie: săritura cu prăjina, viteză pe elan, Microgate